Persuasion of Farmers Toward Kinnow Cultivation - Kuldeep Singh Brar, K.L. Dangi, (Indian Journal of Extension Education, 2022)
The study was conducted in Sri Ganganagar and Sri Karanpur panchayat samities of Sri Ganganagar district. The majority of respondents had expressed favourable persuasion towards kinnow cultivation. It was noticed that farmers had highest degree of agreement with statement i.e. kinnow cultivation is good source of income in farmers’ economy and least level of agreement with statement i.e. proper advice and training for its cultivation is easily available from department of horticulture.